Cucumis melo L. pulp and by-products: Nutritional and antioxidant potential - Silva, M.A. (2022)
Introduction: Nowadays, modern societies are facing two important challenges: (i) demand for healthy foods, due to the increase of chronic diseases; and (ii) reuse food by-products, due to their environmental and economic impacts. Therefore, the valorisation of these food residues, for example, to develop and formulate new food products can be an advantageous approach. Cucumis melo L. is usually consumed as a fruit, but peels and seeds are discarded (1). Objectives: The aim of this study was to evaluate the nutritional composition and antioxidant potential of pulp, peel and seeds of six different Cucumis melo L. varieties (Grand Prix, Soleares, Waikiki, D. Quixote, PIAS and Pele de Sapo). In addition, for Soleares variety a comparison for three different seasons (winter (SW), spring (SS) and autumn (SA)) was performed. Methods: In 2019, the Cucumis melo L. samples were collected from major supermarket chains in the Lisbon region (Portugal). Nutritional composition was analytically determined; the energy value and available carbohydrates were calculated (2-4). Antioxidant activity of Cucumis melo L. was determined using two different methods: DPPH• or 2,2-diphenyl-1-picryl-hydrazyl radical and FRAP or ferric reduction power (5). Moreover, total phenolic content was also assessed by spectrophotometric methodology (5). Results: According to the obtained results, dietary fibre is the main constituent of the seeds, ranging from 42.4 and 49.5 g/100 g, for SA and Waikiki, respectively. The seeds of SS presented the highest fat content (34.9 g/100 g). The protein content of the seeds ranged from 19.6 to 23.0 g/100 g, for SW and SS, respectively. The water is the main constituent (>90%) of the pulp and peel of the six varieties. Regarding total phenolic compounds, SA peel presented the highest content, 385 mg gallic acid equivalents/100 g. Conclusions: Based on the results obtained, the analysed seeds can be considered a good source of dietary fibre, fat and protein. The peel of Cucumis melo L. can be considered a good source of dietary fibre. Moreover, their by-products, are a source of bioactive compounds and could contribute to the intake of natural antioxidants.